Adolescent Fertility Is Lower than Expected in Rural Areas: Results from 10 African HDSS. Issue 2 (11th June 2020) - Rossier, Clémentine; Schoumaker, Bruno; Delaunay, Valérie; Beguy, Donatien; Jain, Aparna; Bangha, Martin; Aregay, Alemseged; Beck, Baptiste; Derra, Karim; Millogo, Modeste; Dube, Albert Nkhata; Siaka, Kone; et al.
Abstract: The adolescent birth rate (ABR) is an important indicator of maternal health, adolescent sexual health, and gender equity; it remains high in sub‐Saharan Africa. While Demographic and Health Surveys (DHS) are the main source of ABR estimates, Health and Demographic Surveillance Systems (HDSS) also produce ABRs. Studies are lacking, however, to assess the ease of access and accuracy of HDSS ABR measures. In this paper, we use birth and exposure data from 10 HDSS in six African countries to compute local ABRs and compare these rates to DHS regional rates where the HDSS sites are located, standardizing by education and place of residence. In rural HDSS sites, the ABR measure is on average 44 percent lower than the DHS measure, after controlling for education and place of residence. Strong temporary migration of childless young women out of rural areas and different capacities in capturing temporarily absent women in the DHS and HDSS could explain this discrepancy. Further comparisons based on more strictly similar populations and measures seem warranted.